2014
DOI: 10.1093/nar/gku1174
|View full text |Cite
|
Sign up to set email alerts
|

DoGSD: the dog and wolf genome SNP database

Abstract: The rapid advancement of next-generation sequencing technology has generated a deluge of genomic data from domesticated dogs and their wild ancestor, grey wolves, which have simultaneously broadened our understanding of domestication and diseases that are shared by humans and dogs. To address the scarcity of single nucleotide polymorphism (SNP) data provided by authorized databases and to make SNP data more easily/friendly usable and available, we propose DoGSD (http://dogsd.big.ac.cn), the first canidae-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 24 publications
0
64
0
Order By: Relevance
“…The novel −74C/G SNP and seven additional canine Oxtr polymorphisms deposited in public databases [dbSNP, Ensembl, DoGSD (Bai et al )] or described in (Kis et al ): −50C/G, −94T/C, −213A/G (formerly: −212A/G), rs22927829, rs8679682 rs8679684 and 19208A/G (formerly: 19131A/G) were genotyped in a larger population involving nearly 700 dogs from 10 breeds and 40 wolves. Our results showed that these SNPs are polymorphic in canines, however, allele frequencies showed marked differences between both species/subspecies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The novel −74C/G SNP and seven additional canine Oxtr polymorphisms deposited in public databases [dbSNP, Ensembl, DoGSD (Bai et al )] or described in (Kis et al ): −50C/G, −94T/C, −213A/G (formerly: −212A/G), rs22927829, rs8679682 rs8679684 and 19208A/G (formerly: 19131A/G) were genotyped in a larger population involving nearly 700 dogs from 10 breeds and 40 wolves. Our results showed that these SNPs are polymorphic in canines, however, allele frequencies showed marked differences between both species/subspecies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To extend the scope of Felidae and Candidae species utilized in this analysis, lion, snow leopard, wolf and grey wolf whole genome sequencing data were incorporated. Wolf (sample: CHW, CRW and ISW) and grey wolf (sample: SolidGW1, LUPWCHN00001 and LUPWRUS00001) SNP variations were downloaded directly from the Dog Genome SNP Database (Bai et al, 2015). For lions and snow leopards, genomic Illumina reads were downloaded (http://biodisk.org) (DOI: 10.1038/ncomms3433), and the Siberian tiger reference sequence was used to call SNPs using the SAMTOOLS-VCFTOOLS pipeline.…”
Section: Evolutionary Analysis Of Genes Involved In Fatty Acid Metabomentioning
confidence: 99%
“…To predict the functional effects of the called variants, SnpEff [11] software together with NCBI annotation release 105 for the CanFam 3.1 genome reference assembly was used. We used a vcf-file containing 648 dog and 8 wolf genomes, which were either publicly available [12,13] or produced during other projects of our group [10]. We excluded 10 genome sequences from other Belgian Shepherd dogs from filtering to minimize the risk of having any unrecognized carriers in the control cohort.…”
Section: Variant Calling and Filteringmentioning
confidence: 99%